2013
DOI: 10.1007/s12010-013-0404-y
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Improvement of Methylglyoxal Synthase Thermostability by His–His Interaction

Abstract: Lately it has been proposed that interaction between two positively charged side chains can stabilize the folded state of proteins. To further explore this point, we studied the effect of histidine-histidine interactions on thermostability of methylglyoxal synthase from Thermus sp. GH5 (TMGS). The crystal structure of TMGS revealed that His23, Arg22, and Phe19 are in close distance and form a surface loop. Here, two modified enzymes were produced by site-directed mutagenesis (SDM); one of them, one histidine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…On the other hand, single mutations H172K and H220D both showed higher thermal sensitivity than the wild type ( Fig 3A ). A likely explanation is that the pair H172/H220 represents a His-His motif, which has been shown that increases protein stability [ 23 25 ]. The loss of the His-His interaction would be compensated by the introduction of the salt bridge.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, single mutations H172K and H220D both showed higher thermal sensitivity than the wild type ( Fig 3A ). A likely explanation is that the pair H172/H220 represents a His-His motif, which has been shown that increases protein stability [ 23 25 ]. The loss of the His-His interaction would be compensated by the introduction of the salt bridge.…”
Section: Discussionmentioning
confidence: 99%